2009
DOI: 10.1002/oti.263
|View full text |Cite
|
Sign up to set email alerts
|

A case study of a five‐year‐old child with pervasive developmental disorder‐not otherwise specified using sound‐based interventions

Abstract: The aim of this study was to determine the efficacy of The Listening Program (TLP) in treating a child with pervasive developmental disorder-not otherwise specified (PDD-NOS). Using a single-subject case study design, one child with PDD-NOS was administered a 20-week TLP intervention focused on improving sensory processing and language function. Data collection included pre- and post-evaluations using video footage, and Sensory Profile and Listening Checklist questionnaires. Results of the study indicated impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Notable changes in the direction and level of the trend lines were noted prior to, during and when the intervention was withdrawn. This directional change is consistent with findings from other studies using a caregiver judgement-based questionnaire measuring the contextual impact of sensory processing on a paediatric client's functional capacities (Hall and Case-Smith, 2007;Nwora and Gee, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Notable changes in the direction and level of the trend lines were noted prior to, during and when the intervention was withdrawn. This directional change is consistent with findings from other studies using a caregiver judgement-based questionnaire measuring the contextual impact of sensory processing on a paediatric client's functional capacities (Hall and Case-Smith, 2007;Nwora and Gee, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…There is a paucity of peer‐reviewed evidence supporting the use of TLP with children diagnosed with ASD; most information is anecdotal at the time of this study. In a single case study, Nwora and Gee () reported mild to moderate improvement in behavioural and sensory tolerance in a 5‐year‐old child with pervasive developmental disorder using TLP. The improvements were determined by comparing pre‐data and post‐data through the Sensory Profile, the Listening Checklist and clinical observations.…”
Section: Self‐stimulatory Behaviours and Sensory Processing Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when evidence appears to be favourable it must be inspected with caution by SLTs. For example, recent single case studies (McCollum 2006, Francis 2007, Nwora and Gee 2009) suggest that listening therapy (a sound therapy derivative of AIT) is beneficial, Nwora and Gee (2009) claiming, for example, that it improved a multitude of skills including behaviour and tolerance, sensory processing, receptive–expressive listening, motor skills and behavioural adjustment. Such an impact across multiple systems is always suspicious and an examination of the measure used to evaluate language is warranted—in this case a judgment based instrument.…”
Section: Reconstructing Ebpmentioning
confidence: 99%
“…A wide range of sound based therapies, such as Binaural Beats, Mozart Effect, Tomatis Method®, Auditory Integration Training, Listening Program®, Samonas, Integrated Listening Systems, and Therapeutic Listening®, are available for use by therapists for children with atypical development (Cassity, Henley, & Markley, 2007;Corbett, Shickman, & Ferrer, 2007;Sinha, Silove, Wheeler, & Williams, 2006). These therapies use modified music or sounds that contain different frequencies, which researchers claim influences the brain (Nwora & Gee, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%